121 A Novel Technique for Infected Metalwork Salvage: Negative Pressure Wound Therapy with Copious Saline Irrigation and Direct Wound Closure Over Dressing. (28th February 2022) - Summers, S.; Daniels, N.; Thahir, A.; Krkovic, M.
Abstract: Aim: Metalwork infection is a challenging complication, often requiring surgical removal. The senior author devised a novel technique consisting of negative pressure wound therapy (NPWT) with high-flow rate saline irrigation and direct skin closure over the standard NPWT dressing. This study aims to evaluate the utility of this modified technique in resolving metalwork infection to allow fracture union without metalwork removal. Method: This is a retrospective chart review of 24 patients (3 upper and 21 lower limb cases) with infected orthopaedic metalwork from a single centre over a seven-year period, who were all managed with this modified technique as an adjunct to standard antibiotic therapy and surgical debridement. Demographic data, surgical data and infectious disease data were collected. Patients were followed up for signs of infection recurrence. Results: 23 of 24 (96%) patient had successful metalwork retention with infection resolution to achieve fracture union. No metalwork was removed due to infection. Original metalwork was maintained in 16 of 24 (67%) patients. The average duration of NPWT was 19 days and the average number of visits to the theatre for NPWT change or removal was 2.5 (mode: 2). Conclusions: This series demonstrates that the modified NPWT technique is an effective adjunct therapy for infected metalwork salvage. This novel technique is safe and reliable with timely resolution of infection to allow fracture union.